The Collapse of Negara Hukum: How Indonesia’s Rule of Law has been Shaped by Embedded Oligarch Politics? - Wiratraman, Herlambang Perdana (UI Scholars Hub, 2025)
This article argues recent performance of the rule of law in the 25-years period after Soeharto’s authoritarian regime. Why has there been a weakening of civil liberties, while on the other hand the oligarchic power and authoritarianism strengthens the current Indonesia’s politics. This article examines the prevalence of arbitrary practices, not only in the fair procedural process of law enforcement, but also why it is so easy to pass anti-democratic laws that contradict the principles of the rule of law. By referring to three specific case studies: free expression, academic freedom and press freedom, this article found that politics in Indonesia have become increasingly cartelized, while at the same time, systemically featured embedded oligarch politics. This starts from cartelized party by designing oligarch-based election trapped into constitutional system. In current politics, Jokowi’s administration represents the re-consolidation and strengthening of ‘new model’ of authoritarianism, which has seriously affected the rule of law, human rights and constitutional democracy, including the fundamental right to freedom of expression. Therefore, unsurprisingly, his political legacies during the Prabowo era and Jokowi's son, Gibran, will work with the same pattern and strategy of exploiting oligarchic power relations in the legal system.